The impact of a csDMARD in combination with a TNF inhibitor on drug retention and clinical remission in axial spondyloarthritis. (22nd March 2022) - Nissen, Michael; Delcoigne, Bénédicte; Di Giuseppe, Daniela; Jacobsson, Lennart; Hetland, Merete Lund; Ciurea, Adrian; Nekvindova, Lucie; Iannone, Florenzo; Akkoc, Nurullah; Sokka-Isler, Tuulikki; Fagerli, Karen Minde; Santos, Maria Jose; et al.
Abstract: Objectives: Many axial spondylarthritis (axSpA) patients receive a conventional synthetic DMARD (csDMARD) in combination with a TNF inhibitor (TNFi). However, the value of this co-therapy remains unclear. The objectives were to describe the characteristics of axSpA patients initiating a first TNFi as monotherapy compared with co-therapy with csDMARD, to compare one-year TNFi retention and remission rates, and to explore the impact of peripheral arthritis. Methods: Data was collected from 13 European registries. One-year outcomes included TNFi retention and hazard ratios (HR) for discontinuation with 95% CIs. Logistic regression was performed with adjusted odds ratios (OR) of achieving remission (Ankylosing Spondylitis Disease Activity Score (ASDAS)-CRP < 1.3 and/or BASDAI < 2) and stratified by treatment. Inter-registry heterogeneity was assessed using random-effect meta-analyses, combined results were presented when heterogeneity was not significant. Peripheral arthritis was defined as ≥1 swollen joint at baseline (=TNFi start). Results: Amongst 24 171 axSpA patients, 32% received csDMARD co-therapy (range across countries: 13.5% to 71.2%). The co-therapy group had more baseline peripheral arthritis and higher CRP than the monotherapy group. One-year TNFi-retention rates (95% CI): 79% (78, 79%) for TNFi monotherapy vs 82% (81, 83%) with co-therapy ( P < 0.001). Remission was obtained in 20% on monotherapy and 22% on co-therapy ( P < 0.001); adjusted OR of 1.16 (1.07, 1.25). Remission rates at 12 months were similar in patients with/without peripheral arthritis. Conclusion: This large European study of axial SpA patients showed similar one-year treatment outcomes for TNFi monotherapy and csDMARD co-therapy, although considerable heterogeneity across countries limited the identification of certain subgroups (e.g. peripheral arthritis) that may benefit from co-therapy.